An Islamic Legal Review of Forced Marriage to a 'Boru Tulang' in Mandailing Custom: A Case Study in Simbolon Village, Padang Bolak Subdistrict, North Padang Lawas Regency - Simamora, Harapan; Pasaribu , Ilhamsyah (Institut Agama Islam Negeri Kendari, 2025)
Marriage in Islam is a sacred bond that must be based on the consent of both parties without any element of coercion. However, in the Mandailing customary community, matchmaking practices that involve coercion are still found, particularly in the tradition of Manyunduti, which involves the marriage between a man and his Boru Tulang (the daughter of the mother's brother). This study aims to describe the practice of forced marriage to a Boru Tulang in Simbolon Village, Padang Bolak Subdistrict, North Padang Lawas Regency, and to analyze it from the perspective of Islamic law. The method used is a qualitative approach with an empirical legal method through interviews with traditional leaders, religious figures, and individuals who have experienced arranged marriages. The results of the study show that this practice is driven by the desire to preserve inherited wealth, strengthen kinship ties, and maintain customary traditions. However, in Islamic law, marriage without willingness contradicts the principles of consent (ridha) and freedom in choosing a spouse. Although a guardian (wali) has the right of ijbar, Islam still emphasizes the importance of the bride and groom's consent. Therefore, matchmaking practices such as Manyunduti need to be re-evaluated to align with the values of justice, public interest (maslahah), and individual rights according to Islamic law